FORMULATION AND EVALUATION OF CRACK CREAM FROM PLANT EXTRACTS - PATIL, VIRENDRA V.; THORAT, YOGESH S.; KOTE, NAGESH S.; HOSMANI, AVINASH H. (International Journal of Current Pharmaceutical Research, 2020)
Objective: The main aim of our research was to develop an anti-cracked heels cream formulation consisting of Hedychium Spicatum, Aloe barbadensis, Azadirachta indica for the treatment of cracked heels. Methods: An anti-cracked heels cream formulation consisting of Hedychium Spicatum, Aloe barbadensis, Azadirachta indica extracts was prepared. Microbiological studies were performed the safety of materials used in the formulation. Results: The developed cream consisting of Hedychium Spicatum, Aloe barbadensis, Azadirachta indica was found to be safe and effective for the treatment of cracked heels. Conclusion: It can be concluded that herbal creams without side effects having anti-inflammatory property can be used as the provision of a barrier to protect the skin.